Pendampingan Lokakarya Perencanaan Pembelajaran 1: Pembelajaran Berdiferensiasi Pembelajaran Yang Berpusat Pada Murid - Muhammad Yahrif; Sriwahyuni (Yayasan Habiburrahman Jamalu Bina Ummat, 2024)
The purpose of this Community Service is to provide assistance to the learning committee in understanding differentiated learning of student-centered learning. Partners in this community service activity are 4 mobilizing schools, namely SMPN 1 Liliriaja, SMPN 3 Liliriaja, SDN 108 Talepu, and SDN 133 Takalala in Soppeng Regency, South Sulawesi Province, consisting of 16 learning committees. The form of activity goes through four stages, namely; 1) presentation of learning materials, 2) Assistance in designing Real Actions, 3) solving problems through lighter questions and 4) Feedback or reflection on activities to all Workshop Participants Learning planning 1. The results of feedback or evaluation showed that 80% of participants answered strongly agree related to the presentation of material and discussion was enough to make the workshop participants understand, then 100% answered strongly agree to the question 'The material presented is according to my needs', and 95% answered very seventh to the question 'My understanding greatly improved after attending the lesson planning workshop 1'. So it can be concluded that this community service activity went well and successfully.